DIFFERENCES PERCEPTION AND INTEREST IN PEATLAND MANAGEMENT POLICY - Zulkarnaini Zulkarnaini; Gevisioner Gevisioner (Jurnal Kebijakan Publik, 2021)
This paper analyzes peatland management policies in Indonesia in general. Contradictions in the regulations and their application will also be an integral part of this discussion. From this contradiction, it is hoped that some general conditions can be understood that are important to underline when looking at the legality of peatland management. The structure of this discussion will begin with an introduction to several regulations related to peat in Indonesia. The research method used is qualitative with a descriptive approach. The analysis used is policy analysis from a legal perspective. The results of the study indicate that peatland management policies have not achieved the desired goals and objectives in their efforts to protect them from damage and extinction. Peatland management has not been followed by changes in the behavior of the community and other stakeholders to preserve biodiversity and implement sustainable development. This is presumably because there are still differences in vision, interests, and perceptions among stakeholders regarding the existence of the peatlands.